Anak Permisif, Anak Bermasalah? Tinjauan Literatur Faktor Pengaruh Pola Asuh Permisif Terlibat Tindak Kriminal - Euodia Alexandra Yuwono; David Hizkia Tobing (Universitas Kristen Maranatha, 2026)
Parents have various approaches to raise their children, one of which is by determining the parenting style used to educate their children. One of the parenting styles is the permissive parenting style. Permissive parenting is characterized by low discipline and boundaries set by parents, and is often associated with low self-control and an increased risk of deviant behavior in adolescents. This study aims to identify the factors that influence the increased likelihood of individuals with a permissive parenting style engaging in criminal behavior. This study was conducted using a literature review method, utilizing 11 articles from the past five years. The literature review identified four factors that increase the likelihood of individuals with permissive parenting styles engaging in criminal behavior: lack of parental supervision and control, parental disregard for children's mistakes, disorientation from norms and rules, and the influence of the environment and peers. The conclusion of this article is that individuals with permissive parenting styles have a higher likelihood of engaging in criminal behavior due to a lack of control, boundaries, and guidance from parents, which results in weak self-control among individuals with permissive parenting styles.